5a+10b-4a-7b=

Simple and best practice solution for 5a+10b-4a-7b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5a+10b-4a-7b= equation:


Simplifying
5a + 10b + -4a + -7b = 0

Reorder the terms:
5a + -4a + 10b + -7b = 0

Combine like terms: 5a + -4a = 1a
1a + 10b + -7b = 0

Combine like terms: 10b + -7b = 3b
1a + 3b = 0

Solving
1a + 3b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3b' to each side of the equation.
1a + 3b + -3b = 0 + -3b

Combine like terms: 3b + -3b = 0
1a + 0 = 0 + -3b
1a = 0 + -3b
Remove the zero:
1a = -3b

Divide each side by '1'.
a = -3b

Simplifying
a = -3b

See similar equations:

| x^4*x^7= | | k=14 | | -(1x+4)=-3x | | 4(a-15)=64 | | 14n+12p+4n+12p= | | 3x-y(5-x)=7 | | p-15=48 | | -2(4)-3(-5)= | | 5k+14m+4k+12m= | | 25(x-y)= | | 4-10.00+x=44 | | 7r+20=41 | | 5*3x=12 | | 2x^2+20x+80=0 | | 3w+16=-8 | | -9f-4+8=-32 | | Y=(x-4)(x-2) | | -20+(-2)(-6)= | | r-30=13 | | -9+11x=10x | | 2+(3n+9)=20 | | 9p-13q+12p+19q= | | x+119+x+59=180 | | 15=-3n-3 | | 20+(2)(6)= | | 13f+7g+3f+4g= | | -3(x-1)+2=4 | | X-3x-9+2=21 | | 2y+2=-5+10y | | 8s+4r+13s+6r= | | V=x(24-2x)(24-2x) | | 2y+7-4y=-17 |

Equations solver categories